The Letters of Moses of Abydos to the Women's Monastic Community (cc 0541): A New Edition and Translation - Angelo, Camille Leon (Journal of Coptic studies, 2024)
The late fifth- and early sixth-century upper Egyptian monastic leader and archimandrite Moses of Abydos penned several letters to the women's community under his leadership. The only extant version of these letters is comprised of six folios (IB.08.07-12) owned by the National Library of Naples. This article provides a much-needed new edition and translation of the extant letters, along with an introduction and commentary, making these letters newly accessible to scholars of late antique Egypt and of monasticism. The introduction provides a technical description of IB.08.07-12: its modern history, physical structure, layout, script, and orthography. Then it considers the content, authorship, and language of the letters and their significance for the study of Egyptian monasticism broadly and women's monasticism specifically. Particular attention is paid to Moses' reliance on Athanasius and Shenoute, what can be gleaned about the women's community under Moses' direction, and the connections between the letters and the monastic epigraphy at the Temple of Seti at Abydos.